Environmental Crime and Contemporary Criminology: Making a Difference - Nobles, Matt R. (American journal of criminal justice, 2019)
The current body of literature on the topic of environmental crime is bigger and better than ever, but the question of whether criminology/criminal justice scholars make a difference in this area is another matter entirely. This paper offers an interpretive view on the strengths and shortcomings in the sub-field of environmental crime, including discussion of the green criminology movement as well as various studies addressing criminal justice system responses to this complex phenomenon. Although this domain has grown steadily since the 1990s, our discipline must change its approach fundamentally in order to maximize the potential for impact. To this end, four major recommendations are directed to the field, along with two overarching messages: (a) environmental crime must move away from the fringes into the criminological mainstream, and (b) participation in this process is open to all motivated criminologists.